The Cyclisation of l-Aryl-2-Benzamidoalkan-l-Ols to 4,5-DihydroOxazoles or Isoquinolines - Md. Sharif, Atan; O. Fitton, Alan (1990)
The cyclisation of several N-benzoyl derivatives of 2-amino-l-phenylpropan-l-ol w~e carried out employing the Pictet-Cams modification ofthe BischlerNapieralski reaction. The formation of4, 5-dihydro-oxazoles orisoquinolines depends on the substituents on the N-benzoyl group. The mode of formation of the products is discussed.